2013
DOI: 10.1152/ajpheart.00067.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific p65 NF-κB deletion protects the injured heart by preservation of calcium handling

Abstract: NF-κB is a well-known transcription factor that is intimately involved with inflammation and immunity. We have previously shown that NF-κB promotes inflammatory events and mediates adverse cardiac remodeling following ischemia reperfusion (I/R). Conversely, others have pointed to the beneficial influence of NF-κB in I/R injury related to its anti-apoptotic effects. Understanding the seemingly disparate influence of manipulating NF-κB is hindered, in part, by current approaches that only indirectly interfere wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 57 publications
3
41
0
1
Order By: Relevance
“…Although MCPIP was reported to promote inflammatory angiogenesis [39,44,47], no significant difference in the immunohistochemically detectable capillary density in the post-MI hearts was observed between the two groups, probably due to targeted MCPIP expression in cardiomyocytes, but not in the endothelial cells or monocytic cells that are known to be involved in postischemic neovascularization [2]. Failing hearts exhibit chronic activation of NF-jB and sustained inflammation [16,29], and blockage of NF-jB has been shown to protect heart from advanced remodeling after MI [17,25,58]. MCPIP was reported to inhibit NFjB activation in other cell types [26,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MCPIP was reported to promote inflammatory angiogenesis [39,44,47], no significant difference in the immunohistochemically detectable capillary density in the post-MI hearts was observed between the two groups, probably due to targeted MCPIP expression in cardiomyocytes, but not in the endothelial cells or monocytic cells that are known to be involved in postischemic neovascularization [2]. Failing hearts exhibit chronic activation of NF-jB and sustained inflammation [16,29], and blockage of NF-jB has been shown to protect heart from advanced remodeling after MI [17,25,58]. MCPIP was reported to inhibit NFjB activation in other cell types [26,49].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes comprises about 20-30 % of all cells within the heart, and they also express TLRs and can be a significant source of innate immune responses [12,15,17,29]. Extensive experimental evidence by gain-and loss-offunction studies suggests that persistent NF-jB activation in cardiomyocytes can cause cardiomyopathy and heart failure by mounting a robust inflammatory response that is common in the context of ischemic injury [17,29,58]. Various approaches that minimize inflammation to the heart have been shown to improve left ventricular remodeling and dysfunction following MI.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with a model of lung injury in which RvD1 reduces inflammation and NF-ĸB through a mechanism involving peroxisome proliferator-activated receptor gamma. 32 Several authors have reported that NF-ĸB inhibition confers cardioprotection, [33][34][35] whereas others suggest that its activation is necessary for cardioprotection. 36 Although we observed NF-ĸB inhibition and reduction of leukocyte accumulation in ischemic regions, we believe that these effects are not sufficient to induce cardioprotection, because similar results were obtained in the 0.01-mg group in which RvD1 had no significant influence on infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…79 Acute NF-κB activation is essential for late cardioprotection induced by ischemic preconditioning. 96, 97 However, mice with cardiomyocyte-restricted overexpression of phosphorylation-resistant IκBα, 98 cardiomyocyte-specific p65 deletion, 99 IκBα overexpression via gene transfer, 100 NF-κB double-stranded decoy DNA transfection, 101 and pharmacological blockade of IκBα 102 or IKKβ 103 have demonstrated that NF-κB inhibition (primarily in cardiomyocytes and perhaps more related to p65) during myocardial I/R decreases infarct size, reduces inflammatory responses including leukocyte infiltration, and improves cardiac function. Studies of non-reperfused MI in mice with cardiomyocyte-restricted overexpression of phosphorylation-resistant IκBα 95 or A20 (NF-κB signaling inhibitor), 104 and IκBα gene transfer 105 have similarly shown that blocking NF-κB (mainly p65 based on time course studies 95 ) attenuates long-term adverse cardiac remodeling, dysfunction, and inflammation.…”
Section: The Inflammatory Phasementioning
confidence: 99%